Makna dan Fungsi Sasta Lisan Mantra Pengobatan Di Daerah Kragan Bagi Generasi Millenial - Nurul Aini (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas PGRI Ronggolawe, 2024)
Mantra is the oldest and oldest literature in Indonesia, spells appear and develop through oral traditions that cannot be separated from oral literature. Oral literature, namely literature which includes the literature of the people which is passed down from generation to generation and passed down orally. Mantras have different characteristics in each region and are subject to change. In the text of the spell there are some words that are difficult to understand and understand. The function of the mantra is that it contains noble values ​​related to certain customs and religions. The method used in this research is descriptive qualitative method. The data in this study are traditional healing spells owned by shamans or psychics in Kragan, Rembang Regency. In this study, researchers are interested in researching the meaning and function contained in the mantra, because the researcher wants to understand the intent and purpose of the meaning or words spoken, so that the millennial generation can now understand and know the